Padrões bioquímicos séricos e hematológicos em bovinos mestiços conforme idade e sexo - De Podesta Junior.Romeu Luiz, Romeu (2017)
This work (study) aimed to establish serum and hematological biochemical patterns of crossbred cattle according to age and sex. 2,741 animals were used, classified into the following categories: 0 to 12 months: 321 females and 192 males; 13 to 24 months: 723 females and 598 males; above 24 months: 527 females and 380 males. The experiment was carried out at Fazenda União rural estate, municipality of Fama, south of MG. The animals selected had normal clinical status. Serum and hematological biochemical examinations were performed by venipuncture of the external jugular vein and 20 mL of blood were collected per animal in vacuum collection tubes, 10 mL without anticoagulant for serum biochemical tests and 10 mL with coagulant for hematological examinations. In the laboratory, the following biochemical parameters were evaluated and analyzed: creatinine, urea, alkaline phosphatase, globulin, albumin, total proteins, glutamic oxalacetic transaminases; gamma glutamyl transferase and calculated the albumin / globulin ratio. For the hematological examinations, the samples were evaluated and analyzed for the serum determinations of red blood cell count; hemoglobin (Hb); hematocrit (Ht); mean corpuscular volume (MCV); mean globular hemoglobin concentration (CHGM); mean corpuscular hemoglobin (HCM); leukocytes (LEU); Segmented neutrophils (NSEG); lymphocytes (LIN); monocytes (MON); eosinophils (EOS) and platelets (PLA). Data were submitted to analysis of variance and compared by Tukey test at a 5% probability level. The serum biochemical variables, creatinine, globulin, PT determined results (p <0.05) in females and males up to 12 months of age and in animals over 12 months of age. AF and GGT determined results (p <0.05) in animals up to 12 months of age and above 12 months of age. TGO determined outcome (p <0.05) in animals between 13 and 23 months of age. Albumin and the A / G ratio did not present differences (P> 005) for the studied variables. Hematological variables, Ht, HCM, NSEG, LIN and EOS determined results (p <0.05) in animals up to 12 months of age and above 12 months of age. MON determined results (p <0.05) in females and males up to 12 months of age and in animals over 12 months of age. Haemocytes, Hb, CHGM, LEU and PLA did not determine differences in results (P> 005) for the variables studied. It is concluded that the work established serum and hematological biochemical patterns in crossbred cattle according to age and sex.